Nesting of an Alien Invasive House Crow Corvus splendens in Verges along Arterial Roads in Dar es Salaam, Tanzania - John, Jasson R. (Tanzania Journal of Science, 2024)
In most cities where little of the original natural vegetation remains, road verges act as home to many urban wildlife. However, the use of road verges for alien avifauna such as House Crow (Corvus splendens) has not been fully documented. This study, conducted between June and July 2021 investigated nesting preferences of the House Crow with particular regards to different verge subdivisions of arterial roads and tree species in Dar es Salaam, Tanzania. Nests were searched in 1813 trees (=42 species) along a stretch of 20 km, and 159 trees (=15 species) were nested with C. splendens. Overall, a total of 257 nests were found on site of which 127 were active. The mean number of nests per tree crown did not vary significantly among the road subdivisions. Nests were positioned between 4 and 16 m above ground in trees with 7.71±2.56 m canopy spread and a mean height of 9.97±2.28 m. For nesting, three tree species were dominant, eight were common, and 31were rare. However, majority of the tree species with the highest nest use ratio were not dominant indicating nesting preference. It is therefore important to consider the influence of tree species on the population of the House Crow during planning for urban verge development. Additionally, managing tree crown is among the best practices to discourage House Crow nesting in urban road verges. Keywords: Alien species; Arterial roads; House Crow; Nest tree preference; Road verges subdivisions